Flexible Electronics: Inkjet Printed Negative Supercapacitors: Synthesis of Polyaniline‐Based Inks, Doping Agent Effect, and Advanced Electronic Devices Applications (Adv. Funct. Mater. 22/2014). (June 2014) - Chiolerio, Alessandro; Bocchini, Sergio; Porro, Samuele
<x xml:space="preserve">Abstract</x> Flexible devices made of doped polyaniline (PANI) are directly deposited by inkjet printing on a plastic sheet (polyimide). The molecular arrangement of the functional material is also represented, showing its crystalline ordering. Inks are synthesized by A. Chiolerio and co‐workers through a water‐based process, avoiding the use of toxic/mutagenic substances normally employed in PANI production. On page 3375, These printed devices show the highest negative supercapacitance measured so far (−2.3 mF @ 30 Hz) corresponding to a specific mass capacity of −799 Fg−1. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>